2015
DOI: 10.1016/j.jmir.2015.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Evidencing Continual Professional Development: Maximising Impact and Informing Career Planning

Abstract: Continuing professional development (CPD) is essential for radiographers to maintain and update their specialised knowledge base in light of constant professional changes. CPD is the continuous and systematic maintenance, improvement, and broadening of knowledge and skills and the development of personal qualities necessary for the execution of professional and technical duties. Professional and regulatory bodies are increasingly relying on proof of CPD through a variety of learning opportunities to provide ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…The tension was between the need to evidence participation, versus the need to evidence learning. Neither system is infallible with literature supporting and highlighting the evident shortcomings of each 31,40,42,43,47,48 . CPD quantification systems have a failing in that they only measure CPD participation not output or even better knowledge translation 43 .…”
Section: Knowledge Skills and Competencymentioning
confidence: 99%
See 2 more Smart Citations
“…The tension was between the need to evidence participation, versus the need to evidence learning. Neither system is infallible with literature supporting and highlighting the evident shortcomings of each 31,40,42,43,47,48 . CPD quantification systems have a failing in that they only measure CPD participation not output or even better knowledge translation 43 .…”
Section: Knowledge Skills and Competencymentioning
confidence: 99%
“…There is an overall identification of poor gap/needs analysis by employers and Radiographers with regard to CPD activity 34,40,52,53,54 . There is a clear need to move forward with impact analysis in the planning, recording and implementation of CPD; taking account of all parties involved -such as the patient, the individual, the service and the profession.…”
Section: Needs/gap Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…An important aspect of the connotation of continuous learning is to maintain the sustainable development of professional competence [11]. There is an important relationship between personal professional development and career aspirations, which can be achieved through professional learning plans and a series of activities [6]. At the same time, career-related continuous learning can help organizational members meet their psychological needs and realize their intrinsic value, thus gaining a competitive advantage in the job market [19].…”
Section: Career Planning's Effect On Individual Continuous Learning Amentioning
confidence: 99%
“…Fairlie and Robb found that, in many small enterprises, technical workers form the backbone of their business and the productivity of these knowledge workers can be divided into six categories: systematization and structuralization, learning motivation, attention, output, punctuality, and communication [5]. Eddy et al regarded self-efficacy and skill sets as a subset of the overall set of abilities required by system engineering and found that the self-efficacy of system engineers can be influenced by a regimented education plan [6]. Therefore, in many countries, educators and managers have used the structured curricula to train engineers, expecting them to acquire technical knowledge, professional skills, and work experience [7,8].…”
Section: Introductionmentioning
confidence: 99%